(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This paper presents the results of a retrospective clinical study of 40 patients who underwent gastrectomy (subtotal or total) for gastric cancer. Case histories were obtained from the Republican Specialized Scientific-Practical Medical Center of Oncology and Radiology of the Republic of Uzbekistan; data were collected over a five-year follow-up period. Survival was assessed depending on the type of operation, sex, disease stage, presence of postoperative complications, and use of adjuvant therapy. It was found that subtotal gastrectomy was associated with higher survival (93%) compared with total gastrectomy (40%), and adjuvant therapy increased survival to 70%.